The synergy between governance and economic integration in promoting female economic inclusion in sub-Saharan Africa - Pamela E. Ofori; Simplice Asongu; Vanessa Tchamyou (African Governance and Development Institute (AGDI), 2021)
The debate on the need for Sub-Saharan African (SSA) countries to increase female participation in the economic sector has intensified the coming into force of the African Continental Free Trade Area (AfCFTA) and good governance. This study investigates the joint effects of governance (comprising of political, economic and institutional governance) and economic integration on female economic participation in sub-Saharan Africa (SSA). The study employs panel data of 42 countries in SSA spanning 1996-2020 for the analysis. The empirical strategy uses the dynamic System Generalized Method of Moments (SGMM) estimation technique. The findings reveal that the single effect of economic integration on female economic participation is necessary but not sufficient. Hence, complementing economic integration with good governance further enhances female economic participation in SSA. In general, the joint effect of economic integration and good governance should be a concern for policymakers to promote female economic inclusion.
Keywords: G20; I10; I32; O40; O55; 330; economic integration; governance; female economic participation; sub-Saharan Africa